Malnutrition defined by Controlling Nutritional Status score was independently associated with prognosis of diffuse large B-cell lymphoma primarily on elderly patients - Fei Wang; Luo Lu; Haoyu Zang; Yanhua Yue; Yang Cao; Min Chen; Yue Liu; Weiying Gu; Bai He (Hematology)
Objectives Controlling Nutritional Status (CONUT) Score is an effective tool for the assessment of malnutrition and proved to be associated with survival of Diffuse large B-cell lymphoma (DLBCL) patients. We investigated the impact of CONUT score on specific subgroups of DLBCL patients, including age and International prognostic Index (IPI) risk groups.Methods Data of 287 newly diagnosed DLBCL in the Third Affiliated Hospital of Soochow University were retrospectively collected. Baseline CONUT score, clinical data and survival information were recorded.Results With the standard cut-off value of 4 points, 88 (30.7%) patients were clarified as malnourished. During a median follow-up of 34 months, malnourished patients exhibited significant reduction in both progression-free survival (PFS) and overall survival (OS). The 3-year PFS rates for malnourished and well-nourished patients were 51.4% and 70.9% (p = 0.001), while the 3-year OS rates were 62.4% and 84.0% (p < 0.001). Malnutrition was demonstrated an independent predictor of OS in DLBCL patients (HR 2.220, 95% CI 1.307–3.772, p = 0.003). It could effectively identify patients with inferior OS in both low/intermediate-low risk and intermediate-high/high risk IPI groups. In the group of elderly patients aged over 60 years, malnutrition was independently associated with OS (HR 2.182, 95% CI 1.178–4.040, p = 0.024), but not PFS (HR 1.709, 95% CI 1.016-2.875, p = 0.070) after adjustment using the Benjamini-Hochberg procedure. Conversely, for younger patients, malnutrition did not demonstrate an independent impact on either PFS or OS.Conclusion Malnutrition evaluated by CONUT score was an independent predictor for the outcome of DLBCL patients, which is exclusively caused by its effect on elderly patients.